2013
DOI: 10.1186/1472-6882-13-98
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of stem bark of Harungana madgascariensis on the red blood cell membrane

Abstract: BackgroundAnemia is a condition that has multiple origins. One such origin is the destruction of red blood cells’ (RBCs) membrane induced by free radicals. Treatment of anemia could therefore be enhanced by the use of free radicals’ scavengers potentially found in some medicinal plants. In this study, the protective effect of Harungana madagascariensis on the RBCs’ membrane physiology was investigated in vitro and in vivo.MethodsIn vitro hemolytic anemia was induced by incubation of fresh human RBCs with carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Indeed the CFH sample has the highest phenolic and flavonoid content between the tested samples. Previous study demonstrated that phenols are good preventers of lipid peroxidation and may be used against deleterious effects of the ROS on cell membrane [10, 13]. In the same way, it has been shown that quercetin may protect mouse erythrocytes from iron-mediated lipid peroxidation by binding iron [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed the CFH sample has the highest phenolic and flavonoid content between the tested samples. Previous study demonstrated that phenols are good preventers of lipid peroxidation and may be used against deleterious effects of the ROS on cell membrane [10, 13]. In the same way, it has been shown that quercetin may protect mouse erythrocytes from iron-mediated lipid peroxidation by binding iron [45].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, humans have developed very complex antioxidant systems both enzymatic (glutathione peroxidase, catalase, and superoxide dismutase) and nonenzymatic (vitamins E and C, thiol antioxidants), which work in synergistic way to protect the cells and organ systems against free radical damage by quenching free radicals and/or chelating redox metals at physiologically related levels [9, 10]. However, under conditions which promote a high state of OS, endogenous antioxidants may not be sufficient [3, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation assay was performed by a formerly described protocol [10]. Phosphate buffer 0.58 mL (0.1 M; pH 7.4), 200 μL sample, 200 μL liver homogenate, and 20 μL ferric chloride (100 mM) were combined to form a mixture, which was placed in a shaking water bath for 1 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In order to contain the harmful effects of ROS, the body has natural antioxidants that are the cell’s defense mechanisms such as glutathione, alpha-lipoic acid, coenzyme Q, ferritin, uric acid, bilirubin, metallothionein, l -carnitine, melatonin, enzymatic superoxide dismutase (SOD), catalase (CAT), glutathione peroxidases (GPXs), thioredoxins (TRX) and peroxiredoxins (PRXs) which scavenge reactive species [9,10,11,12,13]. Despite the presence of the cell’s antioxidant defense system to counteract oxidative damage from ROS, oxidative damage accumulates during the life cycle and the natural defense could be overcome by the ROS [9].…”
Section: Introductionmentioning
confidence: 99%
“…They act as scavengers by donating one of their own electrons in order to replace the stolen electron from free radicals [8,9]. Xylopia aethiopica (Annonaceae) is an evergreen, aromatic tree, largely found in West, Central and Southern Africa.…”
Section: Introductionmentioning
confidence: 99%